PELABELAN L(2,1) PADA OPERASI BEBERAPA KELAS GRAF - Fatimah, S; Sudarsana, I Wayan; Musdalifah, Selvy (Program Studi Matematika, Universitas Tadulako, 2016)
PELABELAN L(2,1) PADA OPERASI BEBERAPA KELAS GRAF